Round Window Stimulation of the Cochlea - Jenkins, Herman A.; Greene, Nathaniel; Tollin, Daniel J. (Frontiers in Neurology, 2021)
Mixed hearing loss associated with a sensorineural component and an impaired conductive mechanism for sound from the external ear canal to the cochlea represents a challenge for rehabilitation using either surgery or traditional hearing amplification. Direct stimulation of the ossicular chain and the round window membrane have allowed improved hearing in this population. The authors review the developments in basic and clinical research that have allowed exploration of new routes for inner ear stimulation. Similar changes occur in the electrophysiological measures in response to auditory stimulation through the traditional route and direct mechanical stimulation of the round window. The latter has proven to be very effective as a means of hearing rehabilitation in a group of patients with significant difficulties with hearing and communication.